G543(P) Severe multisystem haemophagocytic lymphohistiocytosis secondary to herpes simplex virus infection; a case report. (May 2019) - Adonchiyalage, BAS; Fernando, L; Patrick, K
Abstract : Introduction: Haemophogocytic Lymphohistiocytosis (HLH) is a rare potentially lethal haematological condition due to dysregulation of the immune system. HLH can be triggered by viral infections including Herpes Simplex viral (HSV) infection. Here we present a case of severe HLH triggered by HSV type 1 infection. Clinical case: A previously healthy ten-year-old girl was found to have febrile pancytopaenia associated with hepatic dysfunction. Blood investigations revealed hypofibrinogenaemia and very high ferrtin level (>100000 µg/L). She fulfilled the diagnostic criteria for HLH with clear evidence of haemophogocytosis in the bone marrow examination. Despite the initial immunomodulatory treatment (IVIG, Anakinra and Methylprednisalone) her condition rapidly progressed with multisystem involvement (hepatic, respiratory, renal and Central nervous system (CNS)). She needed mechanical ventilation, haemodiafiltration, multiple blood product transfusions and broad spectrum antibiotics. The Aciclovir was initially started with the clinical evidence of CNS disease and continued with the confirmation of HSV type 1 infection (in blood PCR) as the trigger of her HLH. Despite all supportive measures, Aciclovir and immunomodulatory treatments (Dexamethasone, Etoposide, Cyclosporin and Alemtuzumab – monoclonal anti CD52 antibody) her condition was deteriorated with rising ferritin levels (>400, 000 µg/L). The MRI scan of the brain showed evidence of widespread abnormalities. Considering extensive CNS damage, along with severe multisystem failure – unresponsive to HLH therapy, it was concluded to withdraw her care as continuing treatment seemed not in her best interest. Conclusion: HSV infection can trigger severe HLH with multisystem disease. Therefore, in secondary HLH it is important to screen for HSV infection and treat where appropriate. Very high Ferritin level and severe CNS disease are poor prognostic factors in HLH.